Metformin and its Nanoformulations in Cancer Prevention and Therapy - Banerjee, Biswajit; Banerjee, Sabyasachi; Sharma, Tripti; Nandy, Bankim Chandra; Nayak, Amit Kumar; Mondal, Arijit (Current Pharmaceutical Design, 2025)
Currently, the resistance to antineoplastic drugs is an important critical challenge in managing several forms of cancers. An improved prognosis for cancer patients is often associated with increased cell death markers. The objective of the current review article was to discuss how metformin works at the molecular level to fight different types of cancer. This review also discussed the latest developments in metformin nanoformulations and their enhanced anticancer effects and the feasibility of using nanoformulation to deliver metformin with its limitations and challenges. In the current review article, we compiled previously reported studies on metformin's anticancer properties and nanoformulations by searching them in commonly used electronic databases such as Scopus, Google Scholar, PubMed, Medline, Science Direct, etc. In many research investigations, it has been reported that metformin (oral antidiabetic drug commonly employed in the clinical management of type 2 diabetes mellitus), can also help fight cancer by encouraging cell death, mostly through a process called apoptosis. Several previously reported investigations revealed that metformin and its nanoformulations are capable of showing significant anticancer activity against various carcinoma cell lines. From the reported literature, it has been found that there was prominent evidence for anticancer activity of metformin. In addition, a number of studies pointed out that metformin-loaded nanoformulations are capable of showing higher antitumor activity than free metformin, resulting in better efficacy in the therapeutic management of cancer. Metformin-loaded nanoformulations can be employed as potentially useful option for cancer treatment.
Keywords: cancer prevention